دراسة اقتصادية مقارنة لزراعة بذار البطاطا المنتجة بتقنية زراعة الأنسجة والطريقة التقليدية في منطقة الغاب (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
هدفَ البحث إلى دراسة واقع زراعة محصول البطاطا في سورية، وتحديد الاتجاه الزمني العام لتطور المساحة والإنتاج خلال الفترة المدروسة (2002-2011)، وتحديد تكاليف إنتاج البطاطا الربيعية من خلال زراعة نوع البذور المنتجة بتقنية زراعة الأنسجة (Class E) والبذور المنتجة بطريقة الاكثار التقليدية (Class A)، وإجراء التحليل الاقتصادي لمقارنة المؤشرات الاقتصادية. أُجريت الدراسة بالاعتماد على عينة عشوائية بسيطة شملت 172 مزارعاً من مزارعي البطاطا الربيعية في منطقة الغاب لموسم 2011، حيث بيّنت النتائج ارتفاع إنتاجية البطاطا الربيعية عند استخدام نوع البذور (Class E) إلى (3959 كغ/دونم) مقارنة بمتوسط (3508 كغ/دونم) عند استخدام البذور المنتجة بطريقة الاكثار التقليدية (Class A)، غير أنَّ التكاليف الكلية قد ارتفعت في حالة البذور (Class E) إلى (28138.8 ل.س/دونم)، في حين بلغت عند زراعة نوع البذور (Class A) ما قدره (24722.9 ل.س/دونم)، شكلت منها تكلفة البذار ما نسبته (35.2%) و (29.6%)بالترتيب، وبالرغم من ارتفاع التكلفة لدى مزارعي نوع البذور (E) مقارنة بمزارعي النوع (A)، إلا أنهم حققوا ناتجاُ إجمالياً صافياً أعلى من مزارعي النوع (A) بزيادة بلغت (2461.2 ل.س/دونم)، إضافةً إلى قدرة مزارعي النوع (E) على تحقيق ربحاً صافياً من الدونم الواحد بلغ (23328.2 ل.س/دونم) بزيادة بلغت (2447.1 ل.س/دونم) عن مزارعي نوع البذار (A) الذين حققوا ربحاً صافياً بلغ (20881.1 ل.س/دونم). وقد أظهرت الدراسة أن معامل الربحية بالقياس للتكاليف بالنسبة للنوعين (E) و (A) بلغ (82.9%) و (84.4%) بالترتيب، في حين بلغ معامل الربحية بالقياس لرأس المال (72.6%) و (72.7%)بالترتيب.This research aimed to study the reality of the planting potato crop in Syria and determine the general time trend of the area and production development during the period 2002-2011. It aims also to determine the spring potato production costs through the planting of seeds produced by tissue-culture technology (Class E) and seeds produced by traditional multiplication (Class A), and to compare the main economic indicators between the two techniques. The date used was based on a simple random sample surveys of 172 farmers from farmer’s spring potatoes in ALghab region for the 2011 season. Where results showed high spring potatoes productivity when using seeds type (Class E) to (3959 Kg/acre) compared to the average (3508 Kg/acre) when using seeds produced in traditional multiplication (Class A), but the overall costs have increased in the case of seeds (Class E) to(28138.8Sp/acre), while when planting seeds type (Class A), this cost was around (24722.9 Sp/acre), from which the cost of the certified seed represents 35.2% and 29.6% respectively. Despite the high cost of the seed for the farmers type (E) compared to farmers type (A), they have achieved an overall net result higher than farmers type (A). This increase estimated to be around (2461.2Sp/acre). In addition such farmers (Type E) indicates the ability to achieve a net profit for about (23328.2Sp/acre) with an increase of (2447.1Sp/acre) with respect to farmers type (A) who have achieved only a net profit of (20881.1Sp/acre). The study showed that the profitability coefficient measurement of the costs for the two type (E) and (A) was (82.9%) and (84.4%) respectively, while the profitability coefficient measurement with respect to the capital was (72.6%) and (72.7%), respectively.